Psychological Capital and Occupational Well-Being: Mediating Effects of Work Engagement Among Chinese Special Education Teachers - Guo, Qiang; Wang, Yongli; Liu, Qiaoyun; Wang, Tingzhao; Zhang, Lei; Huang, Zhijun; Cao, Shuqin (Frontiers in Psychology, 2022)
This study examines whether psychological capital (PsyCap) indirectly predicts occupational well-being through work engagement among Chinese special education teachers. In total, 615 Chinese special education teachers (female = 567) completed the Psychological Capital Questionnaire, the Special Education Teachers’ Occupational Well-Being Questionnaire, and the Utrecht Work Engagement Scale. The results indicated that PsyCap was positively correlated with occupational well-being and work engagement. Furthermore, work engagement mediated the influence of PsyCap on occupational well-being. Notably, the multiple mediation model indicated that the indirect effects of PsyCap on occupational well-being were mainly due to dedication and absorption. The study’s results illustrate the association between PsyCap, work engagement, and occupational well-being, which may help educational administrators and social workers assist with special education and special education teachers develop and maintain good working conditions.